The Role of Islamic Education Teachers as Role Models in Character Building for Students at SMP Negeri 1 Kunduran - Mustika Faradilla Shanti; Muhammad Wildan Shohib (Journal of Educational Sciences, 2026)
Education plays a crucial role in shaping a nation’s progress, with teachers serving as key agents in guiding students toward moral and intellectual maturity. This study explores the role of Islamic Religious Education (PAI) teachers as moral exemplars in shaping students’ Islamic character at SMP Negeri 1 Kunduran. Using a descriptive qualitative method with a case study approach, data were collected through interviews, observations, and documentation involving PAI teachers, the school principal, guidance counselors, and students. The findings reveal that PAI teachers act not only as educators but also as role models who integrate Islamic values through consistent discipline, politeness, and religious practice. Character formation strategies include modeling behavior (uswah hasanah), moral guidance (mau’idzah hasanah), and habituation through daily activities such as congregational prayers and religious programs. Collaboration between teachers, parents, and the school environment enhances the effectiveness of character building by creating a consistent moral framework both at home and at school. This study concludes that exemplary behavior by PAI teachers significantly influences students’ moral and spiritual development. Future research could explore digital and community-based strategies to strengthen Islamic character education in diverse school settings.